Sleep quality and immune changes in HIV positive people in the first six months of starting highly active antiretroviral therapy (HAART) - Redman, Kirsten (My University, 2016)
Introduction: South Africa has the highest absolute number of persons living with HIV in the world. Previous research has shown that untreated and treated HIV positive patients have sleep disturbances. In a cross sectional pilot study I ran during honours, I showed that sleep disturbances were associated with increased current CD4+ T lymphocyte counts, which may point at a role for immune activation during CD4 reconstitution in the sleep disturbances of South African HIV positive patients. In this study, to better understand sleep disturbances in patients with HIV, I used a longitudinal design and investigated the changes in sleep quality, daytime sleepiness, and the risk of having sleep apnoea as well as the predictors of these changes in HAART-naïve HIV patients, up until at least six months on treatment. Methods: 84 participants were originally enrolled into the study but only 23 (16 women, average age ± SD = 34.4 ± 7.8) came for 3 visits or more after treatment initiation. At all visits, the patients were asked to fill in questionnaires assessing sleep disruption (Pittsburgh Sleep Quality Index, PSQI), daytime sleepiness (Epworth Sleepiness Scale, ESS), risk of sleep apnoea (Berlin Questionnaire, BQ), depression (Beck Depression Inventory, BDI) and pain. In addition, CD4+ T lymphocyte counts, viral loads, body mass index and blood pressure were recorded. We used mixed models analyses in SAS for statistical analyses. Results: The patients had low sleep disruption at baseline (PSQI average ± SD = 5.8 ± 3.3, 52% having a PSQI>5) and when adjusting for depression, sleep quality improved slightly over time (p<0.01). There was moderate daytime sleepiness at baseline (ESS average ± SD = 8.4 ± 4.9) which subsequently decreased over time with patients who had higher log viral loads (>2) showing lower daytime sleepiness than those with low viral loads throughout the study (p<0.01). Higher daytime sleepiness was also reported in patients with higher depression scores (p<0.01). Depression was high at baseline (average BDI score ± SD = 17.8 ± 11) and decreased at 3 months, thereafter with no significant change from baseline (<0.01). BMI was on average high at baseline (25.5± 7.1), in particular in women, and further increased over time (p<0.01), which was associated with a significant increase in the odds of having high risk for sleep apnoea (p<0.01). Rating of pain in the past month decreased over time (p=0.02) and increased pain was associated with increased sleep disruption (p=0.02). Conclusion: Overall, modifiers of sleep-related outcomes (PSQI, ESS, risk of sleep apnoea on the BQ) included depression, pain, viral loads and BMI. Further research would need to assess more metabolic developments in this cohort. Objective measurements of sleep such as polysomnography, and immune measurements such as cytokines will need to be conducted to better explain the underlying mechanisms at play.
This dissertation is submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in fulfilment of requirements for a Master of Science in Medicine Johannesburg, South Africa, 2016
Keywords: Sleep Hygiene; Sleep Wake Disorders; HIV